PENERAPAN METODE UMMI DAN KAISA DALAM KEGIATAN MENGHAFAL AL-QUR’AN PADA SD NEGERI 1 SAWANG KABUPATEN ACEH UTARA - Cardinalia, Tiara (Journal of Contemporary Indonesian Islam, 2024)
The number of phenomena of memorizing the Qur'an only focuses on pursuing memorization targets, but often causes unqualified memorization obtained and even pronunciation and reading are not in accordance with the rules of tajdweed science and to be able to help elementary school students focus more and make it easier to memorize and strengthen memorization of the Qur'an. So that the Ummi and Kaisa methods are applied in memorizing the Qur'an at SDN 1 Sawang North Aceh to meet the school’s goal that students are interested in memorizing the Qur'an with good memorization accompanied by the ability to read the correct Qur'an according to tajweed science. This study consists of several problem formulations, namely: Discussing how the design, application and factors that support and hinder the memorization of the Qur'an at SDN 1 Sawang North Aceh. The research method taken in this thesis is a qualitative approach. So that the results of the research in this thesis can be known that in the process of designing and applying the Ummi and Kaisa Methods to the Qur'an memorization activities have achieved the set targets, although they have faced several obstacles. With details, the first-grade memorization target is 14 Surahs in 1 Semester. Of the total number of students in the Tahfidz class I group, namely 29 students, only 2 people did not meet the target (namely 11 surahs and 13 surahs). As for the Tahfidz class II group consisting of 24 students, all students have reached the memorization target set, namely 20 surahs in 1 semester. From these results, it is hoped that this research can be used as reference material for researchers who will conduct further studies on interesting Qur'an memorization activities using the Ummi and Kaisa methods